Critical Success Factors on Application of E-Commerce in Saudi Arabia - Ali, Eid Abdullah (2010)
Nowadays, E-commerce services used widely in different fields for providing and facilitating user needs. Most of these services give the flexibility and easy to access anytime and anywhere without need to waste the time. Saudi Arabia customers and other internet users are facing a lack in optimizing these services (E-commerce) to do their business and other issues. Hence, this study aimed to determine the critical success factors of optimizing E-commerce application in Saudi Arabia. The study has been addressed the E-commerce application as independent variables and culture, security, and knowledge as dependent variables. The study has been adopted a questionnaire survey for investigating the relationship among the study factors. The analyzing of the variables shows the significant relationship among optimizing E-commerce services by Saudi people are dependent on culture, security, and knowledge.